参考
实践
高级版
登录
简体中文
English
Español
日本語
简体中文 ✔
繁體中文
d
d
x
5
(
6
x
2
−
6
x
+
1
)
\frac{d}{dx} \sqrt{5}(6{x}^{2}-6x+1)
d
x
d
5
(
6
x
2
−
6
x
+
1
)
+
−
.
ln
>
<
×
÷
/
log
≥
≤
(
)
log
x
=
%
选择主题
例子
"(x+1)/2+4=7"
"factor x^2+5x+6"
"integrate cos(x)^3"
更多 »
dif(sqrt(5)*(6*x^2-6*x+1))
differentiate sqrt(5)*(6*x^2-6*x+1)
\frac{d}{dx} \sqrt{5}(6{x}^{2}-6x+1)
1
使用
常数因数法则
:
d
d
x
c
f
(
x
)
=
c
(
d
d
x
f
(
x
)
)
\frac{d}{dx} cf(x)=c(\frac{d}{dx} f(x))
d
x
d
c
f
(
x
)
=
c
(
d
x
d
f
(
x
)
)
。
5
(
d
d
x
6
x
2
−
6
x
+
1
)
\sqrt{5}(\frac{d}{dx} 6{x}^{2}-6x+1)
5
(
d
x
d
6
x
2
−
6
x
+
1
)
2
使用
指数法则
:
d
d
x
x
n
=
n
x
n
−
1
\frac{d}{dx} {x}^{n}=n{x}^{n-1}
d
x
d
x
n
=
n
x
n
−
1
。
5
(
12
x
−
6
)
\sqrt{5}(12x-6)
5
(
1
2
x
−
6
)
完成
sqrt(5)*(12*x-6)
喜欢这个答案?分享它!
Copy Link
我们如何才能使这答案帮到您更多?